2006
DOI: 10.1007/s11259-006-0084-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Variety and Agronomical Conditions on the Level of Polyphenols and Antinutritional Factors of Vicia Faba Minor

Abstract: The faba bean is a legume primarily used in animal feeding as grain and, to a lesser degree, as fodder. As noted, grain, being a good source of amylacea (starch) (45–50% DM) and protein (23–30 CP%DM) of discrete biological value (Verite and Peyraud, 1988), acts as an alternative to soybean which is particularly suitable for organic breeding. Despite this, low productive yields and the presence of thermostable antinutritional factors have reduced the diffusion of this legume especially in feeding non-ruminant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
3
1
Order By: Relevance
“…The high variance of the genotype  location interaction regarding phytic acid (>3 and 7 times larger than that due to location and genotype, respectively) indicates that genotype responded differently to each location. This contrasts with earlier investigation, 31 where phytates were not significantly different among five faba bean genotypes grown at two locations and two seasons in Italy. Cluster analysis based on phytic acid segregated the genotypes into four distinct groups: low, Imposa and AZ10 (e7 g/kg); average, AO1155, Divine, Melodie, Snowbird, and Taboar (8-10 g/kg); above-average, FB25-56, Disco, and NPZ4-7540 (10-12 g/kg); and high, Fatima, Florent, and SSNS-1 (>12 g/kg).…”
Section: ' Results and Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The high variance of the genotype  location interaction regarding phytic acid (>3 and 7 times larger than that due to location and genotype, respectively) indicates that genotype responded differently to each location. This contrasts with earlier investigation, 31 where phytates were not significantly different among five faba bean genotypes grown at two locations and two seasons in Italy. Cluster analysis based on phytic acid segregated the genotypes into four distinct groups: low, Imposa and AZ10 (e7 g/kg); average, AO1155, Divine, Melodie, Snowbird, and Taboar (8-10 g/kg); above-average, FB25-56, Disco, and NPZ4-7540 (10-12 g/kg); and high, Fatima, Florent, and SSNS-1 (>12 g/kg).…”
Section: ' Results and Discussioncontrasting
confidence: 99%
“…The genetic variability in tannin content confirms previous studies in Sicilian faba bean landrace 25 and in Canadian-grown faba bean. 30 Previous studies showed no significant location effect on phenolic content of faba bean genotypes grown in Italy, 31 and only small differences in condensed tannin concentrations (5.16, range = 4.8-5.64 g/kg) among different genotypes grown in replicated plots in six different locations in Manitoba and Saskatchewan in 1972. 30 Antioxidant activity was genotype dependent, ranging from 37.9 to 76.3 mg Trolox equiv (TE)/g dry matter), but unaffected by location.…”
Section: ' Results and Discussionmentioning
confidence: 94%
“…This aspect is very relevant since mineral deficiency or imbalance in feed formulations results in depressed animal growth and poor reproductive performance (McDowell, 2003). In addition, since the seed qualitative parameters of faba bean vary with environmental conditions (Musallam et al, 2004;De Vincenzi et al, 2006), it is imperative to study the variation of seed mineral elements composition in relation to seasonal climatic conditions. The interaction between climate and genotype should also be taken into account to assess more accurately the environmental adaptation of field bean especially under low management cultivation systems.…”
Section: Introductionmentioning
confidence: 99%
“…In a following step, phenylalanine is formed from prephenate and leads to a C-4, C-3, C-9 backbone, to which another ring is added from the acetate/mevalonate pathway [ 31 ]. Geopedological aspects and agronomic techniques have a significant influence on the polyphenol content and related biological activity of the plant extracts [ 32 ]. In the genus L. , two different classes of homoisoflavonoids have been identified: 3-benzylchroman-4-one containing compounds and scillascillin derivatives ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%